Sports medicine staffing patterns and incidence ofiInjury in collegiate men's ice hockey - Baugh, C. M.; Kerr, Z. Y.; Kroshus, E.; Lanser, B. L.; Lindley, T. R.; Meehan, W. P. (Journal of Athletic Training, 2020)
Context: The relative availability of clinicians as well as the types and training of health care providers have been associated with morbidity and mortality in non-athletic health care settings. Whether staffing variations are associated with injury incidence in collegiate athletes is unknown. Objective: To evaluate whether the institutional ratio of athletes to athletic trainers (patient load) or the ratio of staff to nonstaff (graduate assistant and certified intern) athletic trainers or both is associated with the incidence of injuries sustained by male ice hockey athletes at the school. Design: Descriptive epidemiology study. Setting: National Collegiate Athletic Association (NCAA) men's ice hockey teams. Patients or Other Participants: Collegiate men's ice hockey athletes. Main Outcome Measure(s): The NCAA Injury Surveillance Program collected data from collegiate men's ice hockey athletes. Staffing patterns were obtained through telephone interviews. Injury counts, injury rates per 1000 athlete-exposures, and injury rate ratios with 95% confidence intervals were calculated and compared between the following groups: (1) schools with high (versus low) patient load and (2) schools with high (versus low) ratio of staff to nonstaff (graduate assistant and certified intern) athletic trainers. Results: Both the patient load and relative number of staff athletic trainers were associated with variations in the incidences and types of diagnosed injuries in male ice hockey players. Specifically, fewer injuries were diagnosed by clinicians at institutions with high patient loads. The rates of injury overall and non-time-loss injuries were lower in the high patient-load group. Time-loss injury rates, severe injury rates, concussion rates, and overall rates of injury during competition were greater in the group with a higher proportion of staff athletic trainers, whereas non-time-loss injury rates were lower. Conclusions: In this study of collegiate men's ice hockey players, athlete health outcomes were directly related to the number and types of clinicians available. Future researchers should evaluate whether this finding extends beyond men's ice hockey.